(untitled) (Fiep Bulletin - online, 2012)
The chronic disease is a disease with long-term emotional, neuropsychological and social sequelae, as the stigma, it may be incurable and cause restrictions to the patient and his/her quality of life, requiring then the psychologist in the treatment team. The aim of this research was the study of the relation among stigma, public health, Health Psychology and chronic disease in childhood; and also highlight the duties of the Health Psychologist professional in the chronic disease and it stigma context. The methodology was a critical review of the literature. The study brings the conclusion that the stigma in children with chronic diseases (as epilepsy, asthma, diabetes), is a public health issue. There is a tendency to see these problems as stigmatized, with socioeducational, neuropsychological, emotional, organic and financial repercussion. The health professionals area must have an global, clinical, human and social vision of the patient and his/her family situation, considering the total health and public health policies.